Evaluation of Learning Programs in the Economics Education Study Program - Amalina, Endah Nur; Asiah, Afifah Nur (Jurnal Akuntabilitas Manajemen Pendidikan, 2024)
The purpose of this research is to evaluate the Undergraduate Economic Education Study Program, the State University of Malang and Surabaya State University so that it can contribute in the form of information or a picture of program accountability related to service quality, become the basis for determining performance standards and achievement standards that must be achieved and motivate institutions to achieve higher levels of productivity. A mixed method method that applies the CIPP model developed by Guba and Stufflebeam was used in this study to obtain comprehensive results. The research was conducted at  Undergraduate Economic Education, State University of Malang, and Surabaya State University. Based on the evaluation of the CIPP model in the ndergraduate Economic Education study program, the State University of Malang and Surabaya State University, it can be concluded that the two study programs have achieved the excellent category. This is achieved through acquiring A and AQAS international accreditation for both study programs. However, this achievement has yet to 100% meet the criteria of national standards according to applicable regulations, so evaluation and improvement can be carried out to improve the quality of Indonesian education further. The  Undergraduate Economic Education study program of the State University of Malang and Surabaya State University is advised to evaluate educational programs independently and periodically as material for improving and developing study programs following the needs of society and the times, as well as considering policy recommendations that have been prepared in the results of this evaluation research.